2000
DOI: 10.1159/000014252
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Plasma Ceruloplasmin and Transferrin Antioxidant Activities in Preterm Babies

Abstract: Postnatal changes in plasma ceruloplasmin ferroxidase and transferrin iron-binding antioxidant activity were studied in 10 healthy preterm babies during the first 6 weeks of life. Ceruloplasmin levels and ceruloplasmin ferroxidase activity were low at birth, remained stable for the first 3 weeks, and increased between 3 and 6 weeks. The transferrin levels were also low at birth, and this finding persisted throughout the 6-week study period. However, although the plasma iron-binding antioxidant activity was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
3
19
0
1
Order By: Relevance
“…Therefore, we excluded those infants from the study in whom severe asphyxia was present and high FiO 2 oxygen therapy was used. We assume that at normal FiO 2 levels and at normal arterial oxygen tension the free radical burden of the neonate does not become elevated during the first postnatal days, partly due to enhanced anti-oxidant capacity [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we excluded those infants from the study in whom severe asphyxia was present and high FiO 2 oxygen therapy was used. We assume that at normal FiO 2 levels and at normal arterial oxygen tension the free radical burden of the neonate does not become elevated during the first postnatal days, partly due to enhanced anti-oxidant capacity [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between iron deficiency anemia (IDA) and oxidative stress have been investigated by various investigators previously [5,19,20,32]. Increased erythrocyte susceptibility to in vitro oxidative stress [32], decreased antioxidant defense, and increased lipid peroxidation in erythrocytes [19] from adults with IDA have been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that a change in the concentration of peroxide and antioxidants and an increase in the formation of free radicals in infants after EXT. 14 Khatami and et al in a study assessed the serum levels of Iron (Fe) and Zn after EXT and observed an increase in serum Fe and Zn levels following EXT. 15 Khoshdel et al in a study measured glucose and calcium after EXT and revealed a reduction in calcium level and no change in glucose level following EXT.…”
Section: Discussionmentioning
confidence: 99%